2016
DOI: 10.1097/01.prs.0000475798.69478.ea
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of National Institutes of Health Funding on Scholarly Productivity in Academic Plastic Surgery

Abstract: A strong relationship exists between scholarly impact and the procurement of NIH funding. Faculty with greater funding had greater scholarly impact, as measured by the h-index, which suggests that this tool may have utility during the NIH grant application process.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
22
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(24 citation statements)
references
References 20 publications
1
22
1
Order By: Relevance
“…[7][8][9][10][11][12] Within the field of academic plastic surgery, the h-index is shown to predict academic rank and research grant funding. [13][14][15] To date, several studies have identified the academic utility of the h-index among academic plastic surgeons in the United States. [13][14][15][16][17][18][19][20] However, an equivalent study has not been conducted in Canada, and such a study may shine light upon the Canadian research practices in comparison to international colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…[7][8][9][10][11][12] Within the field of academic plastic surgery, the h-index is shown to predict academic rank and research grant funding. [13][14][15] To date, several studies have identified the academic utility of the h-index among academic plastic surgeons in the United States. [13][14][15][16][17][18][19][20] However, an equivalent study has not been conducted in Canada, and such a study may shine light upon the Canadian research practices in comparison to international colleagues.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple recent studies have demonstrated that surgical grant proposals are less likely to get funded (compared to nonsurgical proposals), and if they are funded, it is often for a lesser amount . While there may be increasing barriers for surgeon‐scientists, being able to successfully obtain funding is associated with increasing academic rank and scholarly impact, which has been shown across multiple specialties . Additionally, not only has research funding of an individual been linked to high academic rank, but the funding history of a surgical chairperson has also been linked to the degree of departmental NIH funding …”
Section: Discussionmentioning
confidence: 99%
“…[23][24][25] While there may be increasing barriers for surgeon-scientists, being able to successfully obtain funding is associated with increasing academic rank and scholarly impact, which has been shown across multiple specialties. [26][27][28][29] Additionally, not only has research funding of an individual been linked to high academic rank, but the funding history of a surgical chairperson has also been linked to the degree of departmental NIH funding. 30 The relative value unit (RVU) is one method to gauge the clinical productivity of a physician or surgeon.…”
Section: Discussionmentioning
confidence: 99%
“…Academic plastic surgeons, especially NIH-funded surgeons, occupy a valuable niche in the research landscape. 27 By promoting the open sharing of information, incentive to publish, and freedom from regular profit quotas that can stifle creative risk-taking, academic researchers are at the forefront of innovation in developing novel therapeutics and mechanisms of action. 28 However, they may lack the financial resources and large-scale clinical expertise to navigate economic and legal barriers in translating these ideas from lab bench to patient bedside.…”
Section: Discussionmentioning
confidence: 99%